Early Identification of Prolonged QT Interval for Prevention of Sudden Infant Death - Sarquella-Brugada, Georgia; García-Algar, Oscar; Zambrano, María Dolores; Fernández-Falgueres, Anna; Sailer, Sebastian; Cesar, Sergi; Sebastiani, Giorgia; Martí-Almor, Julio; Aurensanz, Esther; Cruzalegui, Jose Carlos; Merchan, Erika Fernanda; Coll, Mónica; et al. (Frontiers in Pediatrics, 2021)
Introduction: Long QT syndrome is the main arrhythmogenic disease responsible for sudden death in infants, especially in the first days of life. Performing an electrocardiogram in newborns could enable early diagnosis and adoption of therapeutic measures focused on preventing lethal arrhythmogenic events. However, the inclusion of an electrocardiogram in neonatal screening protocols still remains a matter of discussion. To comprehensively analyse the potential clinical value of performing an electrocardiogram and subsequent follow-up in a cohort of newborns. Methods: Electrocardiograms were performed in 685 neonates within the first week of life. One year follow-up was performed if QTc>450ms identified. Comprehensive genetic analysis using massive sequencing was performed in all cases with QTc>470ms. Results: We identified 54 neonates with QTc>450ms/<470ms; all normalized QTc values within 6 months. Eight cases had QTc>480ms at birth and, if persistent, pharmacological treatment was administrated during follow-up. A rare variant was identified as the potential cause of long QT syndrome in five cases. Three cases showed a family history of sudden arrhythmogenic death. Conclusions: Our prospective study identifies 0,14% of cases with a definite long QT, supporting implementation of electrocardiograms in routine pediatric protocols. It is an effective, simple and non-invasive approach that can help prevent sudden death in neonates and their relatives. Genetic analyses help to unravel the cause of arrhythmogenic disease in diagnosing neonates. Further, clinical assessment and genetic analysis of relatives allowed early identification of family members at risk of arrhythmias helping to adopt preventive personalized measures.